The Influence Of Product Quality, Service Quality, And Price On Consumer Purchasing Decisions On Promise Soul Coffee Gedong Meneng, Rajabasa, Unila. - Ardansyah Ardansyah; Rizky Adi Saputra (International Journal of Economics, Business and Innovation Research, 2024)
This research aims to understand and analyze the influence of product quality, service quality and price on purchasing decisions at Janji Jiwa Coffee Gedong Meneng. The population in this research is consumers of Janji Jiwa Coffee Gedong Meneng. The population in this study is unknown. The sample calculation formula for an unknown population uses the Lemeshow formula. So if based on this formula the n obtained is 96.04 = 100 people, then in this research the author must at least take data from a sample of at least 100 people. This analysis uses calculations through statistical methods and to make data analysis easier, this research uses SPSS 25 software. The analysis to be carried out is multiple linear tests, t tests, and coefficient of determination tests. Based on the results of data analysis, it can be concluded that product quality, service quality and price have a positive and significant influence together on purchasing decisions at Janji Jiwa Coffee Gedong Meneng.